Which Radar and ECDIS Functionalities Do Nautical Officers Really Need in Certain Navigational Situations? - Stephanie Hochgeschurz (TransNav: International Journal on Marine Navigation and Safety of Sea Transportation, 2021)
Today’s navigation systems risk information overload and display clutter due to the multitude of available functionalities and information. Different navigational situations present differing challenges to the navigator, because of varying traffic or maneuvering conditions. This suggests that the need for information and functionalities on ECDIS and radar systems depends on the navigational situation, which was investigated by means of an online questionnaire. A sea voyage was divided into three situations, ranging from narrow maneuvering in port areas, to confined navigable waters, and open sea. N = 80 navigators completed the questionnaire. A compound priority measure was calculated to express the need for each functionality. Approximately half of the functionalities were prioritized in a situation dependent manner and substantially more functionalities were prioritized higher on ECDIS than on radar systems. The results have strong implications for aligning navigation systems more with user needs in the sense of a human-centered design approach.